1994
DOI: 10.1128/mcb.14.12.8219
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian nonsense codons can be cis effectors of nuclear mRNA half-life.

Abstract: Frameshift and nonsense mutations within the gene for human triosephosphate isomerase (TPI) that generate a nonsense codon within the first three-fourths of the protein coding region have been found to reduce the abundance of the product mRNA that copurifies with nuclei. The cellular process and location of the nonsense codon-mediated reduction have proven difficult to elucidate for technical reasons. We show here, using electron microscopy to judge the purity of isolated nuclei, that the previously establishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
102
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(110 citation statements)
references
References 43 publications
7
102
0
Order By: Relevance
“…We were unable to amplify by RT ± PCR the hMLH1 gene in HCT116 and TC7 cell lines. Both cell lines are known to have nonsense mutations in hMLH1 (Papadopoulos et al, 1994, and M Muleris, personal communication) and the degradation of the corresponding mRNA could be accelerated by the nonsense-mediated mRNA decay mechanism implicated in mRNA turnover (Belgrader et al, 1994). The LS174T cell line contains a missense mutation within the hMLH1 gene (Deng et al, 1999) which cannot be detected by IVTT.…”
Section: Discussionmentioning
confidence: 99%
“…We were unable to amplify by RT ± PCR the hMLH1 gene in HCT116 and TC7 cell lines. Both cell lines are known to have nonsense mutations in hMLH1 (Papadopoulos et al, 1994, and M Muleris, personal communication) and the degradation of the corresponding mRNA could be accelerated by the nonsense-mediated mRNA decay mechanism implicated in mRNA turnover (Belgrader et al, 1994). The LS174T cell line contains a missense mutation within the hMLH1 gene (Deng et al, 1999) which cannot be detected by IVTT.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the stop codon and its flanking sequences may affect the half-life of mRNA (Belgrader et al, 1994). To test whether these sequences contribute to the instability of the A region, we generated the D40 mutant.…”
Section: Two Cis-acting Elements In the 3 Utr Regulate Gap-43 Mrna Inmentioning
confidence: 99%
“…Terminal structures, namely, the 5Ј cap and 3Ј poly(A) tail, serve as general stabilizing elements found on most mRNAs (7,14). Several internal sequences, such as an AU-rich element (10) or nonsense codons (5), which functionally shorten the half-lives (t 1/2 ) of mRNAs have been identified. Furthermore, an internal element which stabilizes ␣ globin mRNA has recently been identified (38).…”
mentioning
confidence: 99%